1982
DOI: 10.1037/0022-3514.43.1.59
|View full text |Cite
|
Sign up to set email alerts
|

When our identities are mistaken: Reaffirming self-conceptions through social interaction.

Abstract: Although those who have labored to change self-concepts in naturally occurring situations (jave often experienced difficulty, laboratory investigators have reported considerable success in this endeavor. This research sought to reconcile these contradictory findings by examining how people respond behaviorally and psychologically when they receive feedback that disconfirms their self-conceptions. The results showed that self-discrepant feedback produced changes in selfratings only when recipients had no opport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
178
0
6

Year Published

1987
1987
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 394 publications
(196 citation statements)
references
References 10 publications
12
178
0
6
Order By: Relevance
“…Thus in studies by Major et al (1986) and Swann and Ely (1984), targets showed little evidence of behavioral confirmation or self-rating change after interacting with a perceiver who held a self-discrepant expectancy. In addition, targets were less likely to alter their selfconceptions after receiving self-discrepant feedback when they were given an opportunity to refute self-discrepant feedback (Swann & Hill, 1982), when they were supported in their selfconceptions by intimates who view them as they view themselves (Swann & Predmore, 1985), and when they were low rather than high in public self-consciousness ). Markus and Kunda (1986) have suggested that very general self-descriptive measures such as those used in the aforementioned studies are insufficient for revealing how a person adjusts and calibrates his or her self-concept in response to the social environment.…”
Section: The Self (Target) Interprets His or Her Own Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus in studies by Major et al (1986) and Swann and Ely (1984), targets showed little evidence of behavioral confirmation or self-rating change after interacting with a perceiver who held a self-discrepant expectancy. In addition, targets were less likely to alter their selfconceptions after receiving self-discrepant feedback when they were given an opportunity to refute self-discrepant feedback (Swann & Hill, 1982), when they were supported in their selfconceptions by intimates who view them as they view themselves (Swann & Predmore, 1985), and when they were low rather than high in public self-consciousness ). Markus and Kunda (1986) have suggested that very general self-descriptive measures such as those used in the aforementioned studies are insufficient for revealing how a person adjusts and calibrates his or her self-concept in response to the social environment.…”
Section: The Self (Target) Interprets His or Her Own Actionmentioning
confidence: 99%
“…Furthermore, several studies suggest that targets may work especially hard to disconfirm a perceiver's expectancy when they are aware that it is self-discrepant (Swann & Hill, 1982;Swann & Read, 1981b). Simple awareness of the perceiver's expectancy may also be a critical factor in the confirmation process.…”
Section: The Self (Target) Actsmentioning
confidence: 99%
“…Furthermore, if the provided information fails to change the already confirmed perception of an information receiver about the information provider, transparency may still not be achieved. Changing people's perception is not an easy task, and it needs continuous exposure to structured information which utilises their information processing methods [41] and it also requires constant social interactions with the people [71]. Since perception is subjective, different information receivers perceive the same information in different ways, and they respond to information according to their own perception [70].…”
Section: Information Perceptionmentioning
confidence: 99%
“…Koole et al, 2006: p. 214). For example, even people with low self-esteem will avoid positive feedback because it is a threat to their self-concept; those with high self-esteem, however, will welcome positive feedback and react strongly against unfavorable feedback; thus, both groups act in a way that confirms and stabilizes their self-concept (Baumeister, Smart, & Boden, 1996;Swann & Hill, 1982). In sum, since self-esteem may be considered a central aspect of one's identity, and personal identity is a major existential concern, then it is logical to consider selfesteem as part of the self function.…”
Section: Uncertainty About Self (Us)mentioning
confidence: 99%